Value Analysis of Improving College Students’ Physical Education and Mental Health Accomplishments under Curriculum Ideological and Political Education - Jian Liu; Xuemin Deng; Yaohong Liu; Jiancheng Li (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
To provide a significance for the future integration of the concept of "curriculum ideological and political" in physical education institutions across the country. The author conducted a research on the moral alienation of contemporary college students and the implementation of curriculum ideology and politics in basketball teaching in physical education institutions. As well as the dominant and recessive elements that affect the development of basketball teaching in sports colleges across the country, the main and second classes of basketball are analyzed and the results are obtained. The survey was conducted among 450 students on integrating ideological and moral education into basketball teaching. SPSS using software results indicates that 83 students believe that the proportion of rule awareness cultivated in basketball teaching is high, 142 students believe that the proportion of rule awareness cultivated is high, 72 students believe that the proportion of rule awareness cultivated is average, 55 students believe that the proportion of rule awareness cultivated is low, and 53 students believe that the proportion of rule awareness cultivated is low. In the process of basketball teaching, teachers have insufficient guidance concepts for students' mental health, which is detrimental to the reasonable penetration of mental health education in the basketball teaching process, therefore, the development ratio of students' mental health has not been effectively improved. Therefore, it is recommend that teachers can use basketball PE classes to cultivate students' self-confidence. Eliminate students' psychological barriers, improve their interpersonal relationships, and cultivate their team spirit. Promote the all-round development of students' mental health. Moreover, improving college students' physical education and mental health under curriculum ideological and political education can enhance overall well-being, resilience, and civic engagement.